Microstructure and Microwave Dielectric Properties of Low-Temperature Sintering Ca5−yLi2yNi4(VO4)6 Ceramics. (30th July 2021) - Lin, Shih-Hung; Lin, Zi-Qi; Wu, Yu-Ru
Abstract : The influence of sintering temperature and the quantity of lithium content on microstructure and microwave dielectric properties of the Ca5−y Li2y Ni4 (VO4 )6 were investigated. All samples were fabricated by the solid-state reaction method with a sintering temperature of 935 °C–995 °C for 4 h. The results showed no second phases formed from the XRD pattern in all samples and dense surface morphology with a sintering temperature of 965 °C. For specimens with y = 0.10 sintered at 965 °C, the permittivity, quality factor ( Qf ), and temperature coefficient of resonant frequency ( τ f ) were 9.7, 25, 000 GHz –52 ppm/°C, respectively. Thus, these modified dielectric materials possess a high potential for applications in low-temperature co-fired ceramic.